2019
DOI: 10.1055/a-0975-9124
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silybum Marianum on Morphine Addicted Rats, Biochemical Parameters and Molecular Simulation Studies on µ-Opioid Receptor

Abstract: The present study aimed to investigate effects of medicinal plant (Silybum marianum) on the animals with treatment of morphine addiction compared to chemical drug (Naloxane). Also, this study was conducted to evaluate the role of Silybum marianum on factors of serum ALT, AST activities and activity of the antioxidant enzyme:superoxide dismutase (SOD) as well as the extent of lipid peroxidation of Morphine addicted rats.High performance liquid chromatography (HPLC) has been used to measure Morphine in the serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The current study showed that CP caused deterioration in the function and the structure of the liver, as well as induced hepatic oxidative stress, which was expected from previous studies [3,6]. Similar findings have been shown with MOR alone, which was also in line with previous results [17][18][19]. The combined effect of both drugs in the current study caused more or less additive effect on all liver function parameters, as well as the oxidative stress markers, with the exception of MDA and NO, where the effect seemed synergistic.…”
Section: Discussionsupporting
confidence: 93%
“…The current study showed that CP caused deterioration in the function and the structure of the liver, as well as induced hepatic oxidative stress, which was expected from previous studies [3,6]. Similar findings have been shown with MOR alone, which was also in line with previous results [17][18][19]. The combined effect of both drugs in the current study caused more or less additive effect on all liver function parameters, as well as the oxidative stress markers, with the exception of MDA and NO, where the effect seemed synergistic.…”
Section: Discussionsupporting
confidence: 93%
“…Also clinical findings about its galactagogue activity (Di Pierro, Callegari, Carotenuto, & Tapia, 2008) and ovulatory effect in women with PCO (Taher, Atia, & Amin, 2012) shows its effect on female sex hormones. Serotonergic (Rossmanith & Ruebberdt, 2009) and noradrenergic (Osuchowski, Johnson, He, & Sharma, 2004) pathways and opioid receptors (Malekinejad, Taheri‐Broujerdi, Moradi, & Tabatabaie, 2011; Malekshah & Khaleghian, 2019) are other involved pathways in hot flashes which may be modulated by S. marianum (Imenshahidi, Rezaee, Mostofi, & Karimi, 2011; Solati, Yaghmaei, & Mohammdadi, 2012; Yaghmaei, Oryan, Mohammadi, & Solati, 2012). The effect on these receptors can also justify the good effect of this production on improving sleep, mood and other aspects of psychological condition in this study which measured by GCS and HFRDIS.…”
Section: Discussionmentioning
confidence: 99%
“…To understand antitumor activity and the binding site of the target-specific region of compounds, we used molecular docking simulation (Malekshah & Khaleghian, 2019 ). The 3D crystal structures of 1BNA with the sequence, topoisomerase II (PDB ID: 4fm9), anticancer drugs (doxorubicin, mitoxantrone, and trifluridine), ribonucleotide reductase (PDB ID: 3hne1), and triapine were retrieved from RCSB Protein Data Bank and Pubchem.…”
Section: Methodsmentioning
confidence: 99%